The consequences of increasing assertiveness of trans-national religious communities for international relations - Najamudin, Najamudin (State Institute of Islamic Studies (STAIN) Salatiga, 2012)
The transnational communities, or in other terms, the migrant communities whowent to the US and the UK, or to any other European states had strong belief intheir religion in which they might not be contaminated by the secular ideology inthe Western countries. In this respect, the phenomenology of religion in internationalrelations is a relatively new and surprising. Accordingly, this paper aims atinvestigating the implications of the emergence of trans-national religious groupsfor international relations. The paper will argue that the rise of trans-nationalreligious groups has produced a profound impact on international relations. Thefactors that influenced this transformation in international relations is the contemporaryprocesses of globalization which scholars argue, are pivotal to bringingreligion to the centre stage of international relations. In order to deepen theunderstanding of this process, two case scenarios will be analyzed, namely, theSikh Diasporas and the imagined Islamic community, the umma. In this paper, ithas been argued that the rise of trans-national religious actors may affect statesovereignty in one way or another. Under secular ideology, the role of religion ismarginalized from the public sphere, in particular, the domain of politics andÂ religion is being obviously separated. This separation, according to both groups,is problematic. It is therefore, the emergence of Islamic and Sikh communities isconsidered by some liberal democratic countries like India as a peril to its statesovereignty. In Islamic doctrines, the Muslims hold a principle in din wa dawla,the unity of state and religion, while in Sikhism, the Sikhs have to trust miri andpiri, the unification of religious and political institution.Masyarakat transnasional atau dalam terma lain disebut juga sebagai masyarakatmigran yang menetap di Amerika dan Inggris, atau ke negara-negara Eropalainnya memiliki keyakinan yang kuat terhadap agama mereka dan tidakterkontaminasi oleh ideologi sekuler Barat. Pada konteks ini, fenomenologi agamadalam perspektif hubungan internasional merupakan kajian baru dan menarikuntuk dibahas. Berdasarkan hal tersebut, makalah ini bertujuan untuk menyelidikiimplikasi dari munculnya kelompok trans-nasional tersebut terhadap kajianhubungan internasional. Makalah ini berasumsi bahwa munculnya kelompok sosialkeagamaan yang bersifat trans-nasional berdampak besar terhadap hubunganinternasional. Faktor-faktor yang mempengaruhi perubahan ini adalah prosesglobalisasi yang menarik agama ke dalam pola hubungan internasional. Untuklebih jelasnya, dua skenario kasus akan dianalisis, yaitu Diaspora Sikh dan konsepsiâkeummatanâ dalam Islam. Dalam pembahasan makalah ini, didapati bahwamunculnya kelompok masyarakat trans-nasional dapat mengancam kedaulatansuatu negara dalam berbagai bentuknya. Dalam ideologi sekuler, peran agamatermarjinalkan dari ruang publik, khususnya ranah politik. Pemisahan ini, menurutkedua kelompok tersebut, memiliki sejumlah permasalahan. Oleh karena itu,munculnya masyarakat transnasional Islam dan Sikh dianggap oleh beberapanegara demokrasi liberal seperti India sebagai ancaman bagi kedaulatan negara.Dalam perspektif Islam, prinsip din wa dawlah merupakan konsepsi kesatuannegara dan agama, sementara dalam ajaran Sikhisme, doktrin miri piri, merupakankonsepsi penyatuan lembaga keagamaan dan politik.